Justice and Qiṣāṣ in Islamic Law: The Views of Muslim Scholars and Intellectuals at Makassar City, South Sulawesi - Halimang, ST; Ridhwan, Ridhwan; Sakdiah, Sakdiah (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Qiṣāṣ is a legal provision (for those who commit premeditated murder or unlawful acts) that is ontological-theological in nature, which prioritizes justice in the maqāṣid al-sharī'ah paradigm. This form of justice is oriented towards the welfare of humanity while still recognizing the rights and responsibilities of the perpetrator and (family) of the victim. However, qiṣāṣ is often considered barbaric, cruel, and not in accordance with modern human rights standards. Based on this view, it is necessary to study the meaning of justice in qiṣāṣ, according to Muslim scholars and intellectuals in Makassar, South Sulawesi. This study attempts to discuss the construction of the meaning of justice in the law of qiṣāṣ in line with the principles of Islamic law. To answer this, an empirical research method is used with the maqāṣid al-sharī'ah approach. Data were collected through in-depth interviews with informants such as Muslim scholars and intellectuals. The research findings show that qiṣāṣ justice actually fulfills the principles of justice as contained in Islamic law and is in line with theological and sociological dimensions. Qiṣāṣ is applied with a balanced axiological orientation, adhering to the principles of justice. However, the application of the law is hierarchical and depends on the reasons (or motives) for the adjustment. This means that qiṣāṣ is the maximum punishment that can be applied if the evidence of premeditated murder or unlawful association is conclusive and beyond doubt (syubhat). Conversely, if the evidence has strong reasons (such as preventing harm) or is uncertain (syubhat), then the minimum punishment -diyat (financial compensation) - can be applied. In the maqāṣid al-sharī'ah perspective, qiṣāṣ punishment does not only contain the values of justice and welfare because it can save and protect the lives of other humans from someone's evil intentions to kill, so that the goal of Islamic law for the welfare of humanity can be achieved.